Myeloid-Derived Suppressor Cell-Derived Arginase-1 Oppositely Modulates IL-17A and IL-17F Through the ESR/STAT3 Pathway During Colitis in Mice - Ma, Zhanchuan; Zhen, Yu; Hu, Cong; Yi, Huanfa (Frontiers in Immunology, 2020)
Myeloid-derived suppressor cells (MDSC) play a crucial role in regulating the intestinal immune response during colitis. We previously revealed an essential role of MDSC in promoting TH17 cell polarization, which was found to be arginase-1 (Arg-1)-dependent; however, the underlying mechanism remains obscure. Here we report that percentage of MDSC decreased in ArgmyeKO mice during DSS-induced colitis. IL-17A levels reduced but IL-17F levels increased significantly in the colorectum of ArgmyeKO mice, leading to severe tissue damage and high risk of mortality rate. Activation of estrogen receptor (ESR) increased pSTAT3 level in MDSC and consequently led to elevated percentage of MDSC and more Arg-1 and inducible nitric oxide synthase expression in MDSC. Increased level of IL-17A and reduced level of IL-17F alleviated colitis in mice consequently. Together, these findings demonstrate a protective role of MDSC-derived Arg-1 during colitis after activates ESR/STAT3 signaling in MDSC. High level of Arg-1 favors accumulation of IL-17A, but reduced IL-17F expression in the colorectum of mice and ultimately leading to relief of colitis, indicating a potential clinical impact of MDSC-derived Arg-1 for controlling inflammatory bowel disease.